Ancient diversification in extreme environments: exploring the historical biogeography of the Antarctic winged midge Parochlus steinenii (Diptera: Chironomidae) - Maturana, Claudia S.; Contador Mejias, Tamara; Simões, Felipe L.; Valladares, Moisés A.; Vidal, Paula M.; Gañán, Melisa; González-Wevar, Claudio A.; Poulin, Elie; Sands, Chester J.; Convey, Peter (Frontiers in Ecology and Evolution, 2024)
The terrestrial fauna of Antarctica consists of a limited number of species, notably insects, small crustaceans and other micro-invertebrates. Over long periods of evolutionary isolation, these organisms have developed varying degrees of tolerance to multifaceted environmental stresses. Recent molecular biogeographical research highlights the enduring persistence of much of Antarctica’s current terrestrial fauna, with estimates spanning from hundreds of thousands to millions of years. Parochlus steinenii, commonly known as the Antarctic winged midge, stands out as one of the only two insect species native to Antarctica. Distributed across three biogeographic regions, southern South America and the Falkland/Malvinas Islands, sub-Antarctic South Georgia and the Maritime Antarctic South Shetland Islands, this midge raises questions about the temporal isolation of its populations and their divergence. Employing mitochondrial and nuclear genetic markers, we conducted phylogeographic and demographic analyses on 151 individuals of P. steinenii obtained across the three main biogeographic regions including the Magellanic sub-Antarctic Ecoregion (MSE) of southern South America, the sub-Antarctic Island of South Georgia (SG) and the South Shetland Islands (SSI) within the Maritime Antarctic (MA). Our data support the diversification of P. steinenii during the mid-Pleistocene around 1.46 Mya. This period included a branching event between a clade containing only specimens from the MSE and a clade containing individuals from a broader range of locations including the SSI and SG. Based on intraspecific phylogeographic and demographic inferences, we detected strong evolutionary divergence between the three main biogeographic regions. We also detected a signal of population growth during the deglaciation process in SSI and SG, contrary to the pattern seen in the MSE. The different demographic and phylogeographic histories between the sampled biogeographic regions could result from the MA and SG experiencing a strong genetic bottleneck due to a reduction in population size during the Last Glacial Maximum, while the MSE maintained a significant effective population size. The high level of divergence detected between individuals from the MSE and the remaining biogeographic regions supports the hypothesis of a speciation process taking place in P. steinenii.